Using LICHeE and BAMSE for Reconstructing Cancer Phylogenetic Trees. Issue 1 (16th May 2018) - Ricketts, Camir; Popic, Victoria; Toosi, Hosein; Hajirasouliha, Iman
Abstract: The reconstruction of cancer phylogeny trees and quantifying the evolution of the disease is a challenging task. LICHeE and BAMSE are two computational tools designed and implemented recently for this purpose. They both utilize estimated variant allele fraction of somatic mutations across multiple samples to infer the most likely cancer phylogenies. This unit provides extensive guidelines for installing and running both LICHeE and BAMSE. © 2018 by John Wiley & Sons, Inc.